Determination of Free Trade Zone and Free Port Development Area Development in Batam City, Riau Islands, Indonesia - Indera, Edi; Sihombing, Marlon; Muluk, Chairul; ., Rujiman (International Journal of Engineering and Technology, 2018)
Batam Island is built into the Free Trade since 1970 by the Batam Authority, but in 2000 stood Batam City Government, to 2016 the economy grew 6,5%, but since 2017 dropped to 2%, this phenomenon should be a study. The population is employee environment Batam Area Concession Agency, APINDO, BKPM, Batam City Government Employees, the Chamber of Commerce, Community and students. Total respondents 190 respondents sampled (census method). Data Analysis was perfomed using Structural Equation Model (SEM). The software used for the structural analysis is AMOS 22, descriptive analysis using SPSS version 22.0. Geographical Utilization variable determination to variable investmenthas standardized estimate of 0,121<0,50 with CR identical to the value t-tes) CR = 1,749<2,00 on probability = 0,080 > 0,05 is negative not significant. Determination variable to variable Infrastructure Investmenthas standardized estimate 0f -0,816<0,50 with CR identical to the value t-test = -2,013<2,00 on probability = 0,044 < 0,05 is significantly negative. Determination of laten variable to variable organizations Resource investment has standardized estimate of 0,972>0,50 with CR identical to the value t count = 7,336>2,00 on probability = ***<0,05 is a significant positive. Utilization variable determination to variable Geographical Area Developmenthas standardized estimate of 0,020<0,50 with CR idential to value t count = 0,257<2,00 on probability = 0,797> 0,50 is negative not significant. Determination variable to variable Regional Development Infrastructure is has standardized estimate of 0,247<0,50 with CR idential to value t count = 2,248>2,00 on probability = 0,025<0,50 significantly positive. Organization Resource variable determinan variable is the Regional Developmenthas standardized estimate amounted to -0,224<0,50 with CR identical to the value t â€“test = -1,100<2,00 on probability = 0,272>0,50 not significant. Determination variable to variable investment Regional Developmenthas standardized estimate 0,927>0,50 with CR identical to the value t count = 4,900>2,00 on probability = ***<0,05 is a significant positive.Â